Characterising supramolecular architectures in crystals featuring i⋯br halogen bonding: Persistence of X⋯X’ secondary-bonding in their congeners - Tiekink, Edward R. T. * (MDPI, 2021)
The Cambridge Structural Database was surveyed for crystals featuring I⋯Br secondary-bonding in their supramolecular assemblies occurring independently of other obvious supramolecular synthons and devoid of other halogen bonding interactions. In all, 41 crystals satisfied these criteria, with nine examples of zero-dimensional aggregation (uniformly two-molecule aggregates) and 30 one-dimensional chains of varying topology (linear, zigzag and helical). There is one example each of two- and three-dimensional patterns. Type-I, type-II and intermediate bonding situations are apparent; for type-II bonding, the ratio of iodide:bromide functioning as the electrophile is 2:1. Most molecules participated, on average, in one I⋯Br contact, although smaller numbers of half (zero-dimensional) or two contacts (two- and three-dimensional) were observed. The propensity of the formation of related halogen bonding interactions in congeners of the 41 investigated crystals was also studied. Congeners were apparent for 11 crystals, with seven of these exhibiting isostructural relationships, in terms of space-group symmetry and unit-cell parameters. Isostructural relationships do not ensure the formation of analogous aggregation patterns, particularly and in accord with expectation, for the lighter halides. When formed, often distinct aggregation patterns are observed despite the isostructural relationships. Hetero-atomic halogen bonding offers surprises and opportunities in crystal engineering endeavours.